2019
DOI: 10.1021/jacs.8b12291
|View full text |Cite
|
Sign up to set email alerts
|

What Dictates the Spatial Distribution of Nanoparticles within Calcite?

Abstract: Crystallization is widely used by synthetic chemists as a purification technique because it usually involves the expulsion of impurities. In this context, the efficient occlusion of guest nanoparticles within growing host crystals can be regarded as an interesting technical challenge. Indeed, although there are various reports of successful nanoparticle occlusion within inorganic crystals in the literature, robust design rules remain elusive. Herein, we report the synthesis of two pairs of sterically-stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 69 publications
4
72
0
Order By: Relevance
“…Under these conditions,b oth step lengths and kink sites are more prevalent, which facilitates nanoparticle occlusion. [18] More uniform, dense nanoparticle occlusion can be achieved at higher anionic phosphate contents (see Figure 2d-f). This is because there are now sufficient anionic groups to ensure strong binding to the crystal surface,w hich leads to nanoparticle engulfment by the advancing steps.C aCO 3 crystals precipitated in the presence of an equivalent molar concentration of each of the water-soluble macro-CTAs used in this study (e.g.…”
Section: Angewandte Chemiementioning
confidence: 95%
See 2 more Smart Citations
“…Under these conditions,b oth step lengths and kink sites are more prevalent, which facilitates nanoparticle occlusion. [18] More uniform, dense nanoparticle occlusion can be achieved at higher anionic phosphate contents (see Figure 2d-f). This is because there are now sufficient anionic groups to ensure strong binding to the crystal surface,w hich leads to nanoparticle engulfment by the advancing steps.C aCO 3 crystals precipitated in the presence of an equivalent molar concentration of each of the water-soluble macro-CTAs used in this study (e.g.…”
Section: Angewandte Chemiementioning
confidence: 95%
“…Zuschriften statistical copolymerization of the non-ionic Gmonomer with the anionic Pmonomer while targeting aconstant intermediate DP of around 50 can avoid such problems.P rior studies showed that P 32 -B 300 nanoparticles are surface-confined [18] while (P 32 -stat-G 13 )-B 300 are uniformly occluded. This is most probably because the latter stabilizer chains can adopt more conformations.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…DP=100) should result in smaller nanoparticles with relatively low stabilizer surface densities . More importantly, a relatively short stabilizer chain DP is expected to restrict the conformational entropy of the stabilizer chains, hence leading to weaker nanoparticle binding to the growing crystal surface and reducing nanoparticle occlusion . Conveniently, statistical copolymerization of the non‐ionic G monomer with the anionic P monomer while targeting a constant intermediate DP of around 50 can avoid such problems.…”
Section: Methodsmentioning
confidence: 99%
“…Conveniently, statistical copolymerization of the non‐ionic G monomer with the anionic P monomer while targeting a constant intermediate DP of around 50 can avoid such problems. Prior studies showed that P 32 ‐B 300 nanoparticles are surface‐confined while (P 32 ‐ stat ‐G 13 )‐B 300 are uniformly occluded. This is most probably because the latter stabilizer chains can adopt more conformations.…”
Section: Methodsmentioning
confidence: 99%